Model Generalized Poisson Regression (GPR) pada Faktor-Faktor yang Mempengaruhi Jumlah Kasus Stunting di Kabupaten Kupang, Provinsi Nusa Tenggara Timur (NTT) - Jeharu, Bernadinus; Guntur, Robertus Dole; Ginting, Keristina Br.; Pahnael, Jusrry Rosalina (ESTIMASI: Journal of Statistics and Its Application, 2026)
Stunting is a condition of failure to thrive due to chronic malnutrition, recurrent infections, and poor sanitation. East Nusa Tenggara (NTT) Province is the highest contributor of stunting cases in Indonesia and Kupang Regency is also the third highest contributor of stunting cases in NTT Province. This study aims to identify factors that influence the number of stunting cases using the Generalized Poisson Regression (GPR) model which is able to overcome overdispersion in count data. Secondary data for 2023 was obtained from the Kupang District Health Office and BPS. Independent variables included LBW, complete basic immunization (IDL), exclusive breastfeeding, nutritional status of children under five, access to sanitation and safe drinking water, vitamin A administration, number of health centers, and health workers. The results of the analysis show that the percentage of IDL toddlers, the percentage of neighborhoods with access to safe drinking water, the number of infants receiving Vitamin A, exclusive breastfeeding, the number of health centers, and the number of community health workers have a significant effect on the number of stunting cases in Kupang district. These findings can inform the formulation of more effective health intervention policies in the region.